2024
DOI: 10.1111/cts.13704
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world implementation of DPYD and UGT1A1 pharmacogenetic testing in a community‐based cancer center

Megan Muldoon,
Mollie Beck,
Nichlas Sebree
et al.

Abstract: We set out to demonstrate the feasibility of pharmacogenetic testing of DPYD and UGT1A1 and explore the clinical benefits in a community‐based cancer center. We conducted a retrospective review of 280 patients who underwent pharmacogenetic testing between November 2020 and May 2023. The primary end points included the percentage of patients with results prior to chemotherapy initiation, percentage of DPYD‐ and UGT1A1‐guided interventions implemented before chemotherapy initiation, and the turnaround time (TAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Academic teaching institutions/hospitals comprised >70% of the sites that conducted pre-treatment DPYD testing. Relative to community oncology clinics, these tertiary cancer centers typically have greater access to nancial and technical resources and PGx expertise [13,31,32]. These resources are critical to implementing robust system-wide strategies for clinical PGx adoption including interruptive alerts in the EMR [13], or integrating testing into medication order sets [13,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Academic teaching institutions/hospitals comprised >70% of the sites that conducted pre-treatment DPYD testing. Relative to community oncology clinics, these tertiary cancer centers typically have greater access to nancial and technical resources and PGx expertise [13,31,32]. These resources are critical to implementing robust system-wide strategies for clinical PGx adoption including interruptive alerts in the EMR [13], or integrating testing into medication order sets [13,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to community oncology clinics, these tertiary cancer centers typically have greater access to nancial and technical resources and PGx expertise [13,31,32]. These resources are critical to implementing robust system-wide strategies for clinical PGx adoption including interruptive alerts in the EMR [13], or integrating testing into medication order sets [13,31,32]. A recent study from Dana-Farber Cancer Institute reported an increase in pre-treatment DPYD testing frequency from 14% to 89% after implementing a system-wide testing program that included automated interruptive alerts at the time of initial FP chemotherapy order [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Real‐world data from a cancer patient population that underwent DPYD and UGT1A1 pharmacogenetic testing were the subject for the paper by Muldoon et al. 4 The objective of the retrospective analysis of these RWD was to demonstrate the feasibility of the DPYD and UGT1A1 pharmacogenetic testing prior to starting chemotherapy in these patients, specifically for community‐based cancer centers. Operationally, it was shown that the majority of the pharmacogenomic results were available and interpreted before chemotherapy initiation.…”
mentioning
confidence: 99%